Dampak Pencatatan dan Jatuh Tempo Waran terhadap Harga Saham yang Disertai Waran di Indonesia - Stefan Suryawinata; Aldwin Tekadtuera; Dahlia Ervina (Universitas Prasetiya Mulya, 2020)
Abstract. This research discusses the stock abnormal return effect of warrants to itsunderlying stock on its listing and maturity date. The sample that is being used for this study is thestock price changes of stocks backed with warrant in Indonesian stock market for the year 2008 to2018. Using event study approach to observe stock abnormal return effect on the listing and maturitydate of warrants. The results of this research are that we find a significant negative abnormal returnaround the warrants’ listing date. On the warrants’ expiration date, we find a signifiant negativeeffect before and after maturity date of in the money warrants. However, a different result is obtainedfor the observation of out of the money warrants which does not show any significant abnormal returnon the event window.